Writing CSS with LESS - Wimberly, Walter (InfiniteSkills, 2013)
"In this Writing CSS with LESS training course, expert author Walter Wimberly teaches you everything you need to know about this dynamic stylesheet language. This course is designed for users that already have a working knowledge of CSS. You will start out by learning how to build LESS files, on the client-side and server-side. Walter will teach you how to build consistent values, including how to modify the value and scope of a variable, use Mixins, and identify Syntax errors. From there, you will learn about Nesting, and how to use Nesting with multiple selectors and pseudo-classes. This video training will also teach you about the functions and operations in LESS, including defined LESS functions in colour and math. Finally, Walter will show you how to compile LESS to CSS. By the completion of this video based training course, you will have an in-depth understanding of how to write CSS with LESS. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.